Bilateral lung transplantation for pediatric pulmonary arterial hypertension: perioperative management and one-year follow-up - Jack, Thomas; Carlens, Julia; Diekmann, Franziska; Hasan, Hosan; Chouvarine, Philippe; Schwerk, Nicolaus; Müller, Carsten; Wieland, Ivonne; Tudorache, Igor; Warnecke, Gregor; Avsar, Murat; Horke, Alexander; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background. Bilateral lung transplantation (LuTx) remains the only established treatment for children with end-stage pulmonary arterial hypertension (PAH). Although PAH is the second most common indication for LuTx, little is known about the optimal perioperative management and midterm clinical outcome. Methods. Prospective observational study on consecutive children with PAH who underwent LuTx with scheduled postoperative VA-ECMO support at Hannover Medical School from December 2013 to June 2020. Results. 12 PAH patients underwent LuTx (mean age 11.9 years; age range 1.9-17.8). Underlying diagnoses included idiopathic (n=4) or heritable (n=4), PAH associated with congenital heart disease (n=2), pulmonary veno-occlusive disease (n=1) and pulmonary capillary hemangiomatosis (n=1). Mean waiting time was 58.5 days (range 1-220d). Three patients were bridged to LuTx on VA-ECMO. Intraoperative VA-ECMO/cardiopulmonary bypass was applied and VA-ECMO was continued postoperatively in all patients (mean ECMO-duration 185h; range 73-363h; early extubation). The median postoperative ventilation time was 28h (range 17-145h). Twelve months after LuTx, all patients had normal biventricular systolic function by means of echocardiographic 2D- and strain analysis. All PAH patients are alive 2 years after LuTx (median follow-up 53 months, range 26-104 months). Conclusion. LuTx in children with end-stage PAH resulted in excellent midterm outcome (100% survival 2 years post-LuTx). Post-operative VA-ECMO facilitates both, early extubation with rapid gain of allograft function, and sustained biventricular reverse-remodeling and systolic function after RV pressure unloading and LV volume loading.